Convert the vector A = xy ax - 2x ay to cylindrical system.
Given vector,
"A=xy(a_x-2xa_y)"
"\\Rightarrow A= xya_x-2x^2ya_y"
Now, "x=a\\cos\\theta"
"y=a\\sin\\theta"
"z=z"
"B=a\\cos\\theta\\times a\\sin\\theta\\times a_y-2\\times (a\\cos\\theta)^2\\times a\\sin\\theta\\times a_y"
we know that "a=a_x= a_y" for the circle
"=a^3(cos\\theta.\\sin\\theta-2\\cos^2\\theta.\\sin\\theta )"
"=a^3(\\frac{1}{2}\\sin2\\theta-cos\\theta. \\sin2\\theta)"
"=a^3\\sin2\\theta(\\frac{1-2\\cos\\theta}{2})"
"=\\frac{4a^3\\sin2\\theta \\cos^2(\\frac{\\theta}{2})}{2}"
"=2a^3\\sin2\\theta \\cos^2(\\frac{\\theta}{2})"
Comments
Leave a comment